Endogenous Type I-C CRISPR-Cas system of Streptococcus equi subsp. zooepidemicus promotes biofilm formation and pathogenicity - Xie, Honglin; Zhang, Riteng; Li, Ziyuan; Guo, Ruhai; Li, Junda; Fu, Qiang; Wang, Xinglong; Zhou, Yefei (Frontiers in Microbiology, 2024)
Streptococcus equi subsp. zooepidemicus (SEZ) is a significant zoonotic pathogen that causes septicemia, meningitis, and mastitis in domestic animals. Recent reports have highlighted high-mortality outbreaks among swine in the United States.Traditionally recognized for its adaptive immune functions, the CRISPR-Cas system has also been implicated in gene regulation, bacterial pathophysiology, virulence, and evolution. The Type I-C CRISPR-Cas system, which is prevalent in SEZ isolates, appears to play a pivotal role in regulating the pathogenicity of SEZ. By constructing a Cas3 mutant strain (ΔCas3) and a CRISPR-deficient strain (ΔCRISPR), we demonstrated that this system significantly promotes biofilm formation and cell adhesion. However, the deficiency in the CRISPR-Cas system did not affect bacterial morphology or capsule production. In vitro studies showed that the CRISPR-Cas system enhances pro-inflammatory responses in RAW264.7 cells. The ΔCas3 and ΔCRISPR mutant strains exhibited reduced mortality rates in mice, accompanied by a 带格式的: 编号方式: 连续 decreased bacterial load in specific organs. RNA-seq analysis revealed distinct expression patterns in both mutant strains, with ΔCas3 displaying a broader range of differentially expressed genes, which accounted for over 70% of the differential genes observed in ΔCRISPR. These genes were predominantly linked to lipid metabolism, the ABC transport system, signal transduction, and quorum sensing. These findings enhance our understanding of the complex role of the CRISPR-Cas system in SEZ pathogenesis and provide valuable insights for developing innovative therapeutic strategies to combat infections.